2010
DOI: 10.1245/s10434-010-1154-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Hepatic Neuroendocrine Tumor Metastasis: Results from an International Multi-Institutional Analysis

Abstract: Liver-directed surgery for NELM is associated with prolonged survival; however, the majority of patients will develop recurrent disease. Patients with hormonally functional hepatic metastasis without prior extrahepatic or synchronous disease derive the greatest survival benefit from surgical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
355
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(378 citation statements)
references
References 19 publications
15
355
2
6
Order By: Relevance
“…Liver metastases accounts for about 90% of the distant metastases of PNET and is a major prognostic factor for this tumor [2,10,11]. Previous researchers have reoprted that the concurrent resection of both the primary lesion and resectable liver metastases is feasible and might improve the prognosis [3][4][5][6]. Palliative cytoreductive surgery refers to the removal of most of the metastasis (>90% of the lesion), during which the concurrent or staged resection of the primary lesion or liver metastases may be considered according to ENETS consensus guidelines [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver metastases accounts for about 90% of the distant metastases of PNET and is a major prognostic factor for this tumor [2,10,11]. Previous researchers have reoprted that the concurrent resection of both the primary lesion and resectable liver metastases is feasible and might improve the prognosis [3][4][5][6]. Palliative cytoreductive surgery refers to the removal of most of the metastasis (>90% of the lesion), during which the concurrent or staged resection of the primary lesion or liver metastases may be considered according to ENETS consensus guidelines [12].…”
Section: Discussionmentioning
confidence: 99%
“…PNET remain an important clinical issue due to the high incidence of metastatic rate, and the lack of an evidenced-based treatment strategy [3][4][5][6]. Liver is the most common place for PNET distance metastasis, and literature reports showed a 46% to 93% hepatic metastasis rate [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mayo et al [6] reported the outcomes of 339 patients from 8 major hepatobiliary centers who underwent surgical management for neuroendocrine liver metastasis (NELM) from 1985 to 2009. Major hepatectomy was performed in 45% of patients, and 14% underwent a second liver operation.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…Current opinions suggest extended surgical indications for P-NET patients with liver metastases, because survival is improved and P-NET is a slow-growing tumor [1,[6][7][8][9] . For liver metastasis without extrahepatic metastasis, standard/aggressive surgery is the first choice for well-differentiated P-NET categorized as GEP-NET G1/G2 [1,7,8] .…”
Section: Resection Of Liver Metastasesmentioning
confidence: 99%
“…Some cur-MINIREVIEWS rent opinions suggest an expanded surgical indication for P-NET patients with liver metastases, because survival is improved [1,[6][7][8][9] . Aggressive surgery for liver metastases or cytoreductive surgery for over 90% of the visible tumors are important to improve survival [6,9] . Cytoreductive surgery for liver metastases is indicated to reduce hormone levels and improve clinical symptoms and prognosis [1,6,9] .…”
Section: Introductionmentioning
confidence: 99%